2011
DOI: 10.5455/vetworld.2011.485-491
|View full text |Cite
|
Sign up to set email alerts
|

Spirocercosis in stray dogs of Chittagong metropolitan area of Bangladesh: an epidemiological and pathological investigation

Abstract: A total of sixty adult stray dogs (32 male and 28 female) randomly captured from different locality of Chittagong metropolitan area were euthanized during the period of May 2010 to January 2011. The dogs were necropsized to observe the presence of Spirocerca lupi in their oesophagus producing characteristic nodular lesions. The associated haematological changes were also determined. Twenty four (40%) of the captured dogs were positive (40.62 % male and 39.28 % female) for spirocercosis having oesophageal nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The current study first identified a considerable diversity of intestinal parasites from free‐ranging canids in the study area and Nepal. The current prevalence rate of intestinal parasites (95.7%; n = 332) was on par with the report of stray canids from Bangladesh (95%; n = 60) (Das et al., 2012), lower than from Ethiopia (100%; n = 13) (Jones et al., 2011) and India (99%; n = 101) (Traub et al., 2014) but was higher than from Nepal (56.2%–78.5%; n = 105–157) (Satyal et al., 2013; Yadav & Shrestha, 2017), India (90.7%; n = 108) (Sudan et al., 2015), South Africa (82.5%; n = 240) (Mukaratirwa & Singh, 2010), Malaysia (87.7%, n = 77 to 88.3%, n = 227) (Ngui et al., 2014; Tun et al., 2015) and Vietnam (55.5%, n = 200) (Ng‐Nguyen et al., 2015). It indicates that the prevalence rate of intestinal parasites is different in different countries; these variations might be due to the difference in geo‐climatic factors, sample size, sampling breed, sampling season, treatment strategy and methodological contrasts.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The current study first identified a considerable diversity of intestinal parasites from free‐ranging canids in the study area and Nepal. The current prevalence rate of intestinal parasites (95.7%; n = 332) was on par with the report of stray canids from Bangladesh (95%; n = 60) (Das et al., 2012), lower than from Ethiopia (100%; n = 13) (Jones et al., 2011) and India (99%; n = 101) (Traub et al., 2014) but was higher than from Nepal (56.2%–78.5%; n = 105–157) (Satyal et al., 2013; Yadav & Shrestha, 2017), India (90.7%; n = 108) (Sudan et al., 2015), South Africa (82.5%; n = 240) (Mukaratirwa & Singh, 2010), Malaysia (87.7%, n = 77 to 88.3%, n = 227) (Ngui et al., 2014; Tun et al., 2015) and Vietnam (55.5%, n = 200) (Ng‐Nguyen et al., 2015). It indicates that the prevalence rate of intestinal parasites is different in different countries; these variations might be due to the difference in geo‐climatic factors, sample size, sampling breed, sampling season, treatment strategy and methodological contrasts.…”
Section: Discussionmentioning
confidence: 49%
“…The current prevalence rate of intestinal parasites (95.7%; n = 332) was on par with the report of stray canids from Bangladesh (95%; n = 60) (Das et al, 2012), lower than from Ethiopia (100%; n = 13) (Jones et al, 2011) and India (99%; n = 101) (Traub et al, 2014) animal carcasses, leftover foods, garbage, animal dung and human faeces. Furthermore, they also lick water from contaminated sources that contribute to parasitosis.…”
Section: Discussionmentioning
confidence: 65%
“…Examples come from Israel [94], Jamaica [94], Egypt [97], Brazil [98,99], Lousiana [100], Central America [23,78], Kenya [72,[101][102][103], India [104][105][106]. Some of the more recent investigations were carried out in South Africa [92,[107][108][109], Iran [110], Bangladesh [111], Israel [95,112,113], and America [114][115][116]. Since malignant esophageal neoplasms are extremely uncommon in locations without spirocercosis [115], it was easier to prove a causal relationship [68].…”
Section: Spirocerca Lupimentioning
confidence: 99%
“…Em Granada, na Espanha, a prevalência da espirocercose em cães com donos e errantes foi, respectivamente, de 8,8% e 14,2% (3). Caninos errantes geralmente não são submetidos a tratamento profilático com vermífugos e estão mais susceptíveis à infecção quando ingerem larvas infectantes L3 de Spirocerca lupi, contidas em besouros coprófagos, aves, répteis ou roedores (6). As condições climáticas, caracterizadas por altas temperaturas e alta queda pluviométrica durante o verão, e a deficiente infraestrutura de recolha e gestão de resíduos sólidos podem contribuir para a ocorrência da parasitose em cães errantes na cidade da Matola.…”
Section: Relato De Casounclassified
“…O tamanho dos nódulos e a localização dos nódulos parasitários no terço posterior da porção torácica do esôfago corroboram os achados descritos por outros autores (4,6,21). Em casos de migração errática, larvas do parasito podem enquistar no estômago, vértebras, pleura, artéria aorta, rins, mediastino, tecido nervoso central e pele, resultando em sinais clínicos atípicos da parasitose (3,10,12,13,24,25,28).…”
Section: Relato De Casounclassified